Gambaran Faktor Risiko Kontaminan Biologi pada Uji Lingkungan di RSU “Y” Surabaya - Mochamad Rizal Maulana; Khuliyah Candraning Diyanah; Fransisca Susilastuti (Media Kesehatan Masyarakat Indonesia, 2020)
Hospitals as a place of health care and workplace have a variety of potential hazards that can harm health. One of the efforts of the hospital environment can be done by conducting supervision and inspection. The purpose of this research, to describe the risk factors of biological contaminants in the environmental test results conducted in Surabaya General Hospital "Y". This research was descriptive research with a cross-sectional approach. This research uses secondary data of the laboratory test results of BBTKLPP Surabaya in 2015-August 2017, as well as literature from several sources to support the data available. Data were analyzed in a descriptive and presented in the form of tables and graphs. The results of biological examinations on air space, food and beverage, medical device swab, air conditioner, and clean water in unqualified conditions. Only the quality of the wall swab and floor can be said to be good and qualified. Public hospital "Y" Surabaya is still not qualified in terms of quality microbiology tests based on the decree of the Minister of Health of the Republic of Indonesia number 1204 the year 2014 on health requirements of the hospital environment. A thorough evaluation is necessary to improve the quality of microbiology in the environment in the hospital Y Surabaya, especially in areas with high risk such as surgical rooms and ICU.